JOINT EFFECT OF THE FRESH AND FERMENTED MILK FORMULA AMONG 6 MONTHS AGED INFANTS, SUFFERING FROM THE FUNCTIONAL DIGESTION DISORDERS - T.N. Elkina; E.A. Surovikina ("Paediatrician" Publishers LLC, 2008)
Recurrence of the functional digestion disorders among 6 months aged infants, undertaking artificial feeding, is extremely high. The article reviews the findings on the application of the adapted milk formulas Nutrilak 0-6 and Nutrilak km combination to correct the above said disorders without drug intervention. Key words: functional digestion disorders, 6 months aged infants, adapted fermented milk formulas.